Financialization in Kaleckian economies with and without labor constraints - Soon Ryoo; Peter Skott (University of Massachusetts, Department of Economics, 2008)
Most Kaleckian models assume a perfectly elastic labor supply, an assumption that is questionable for many developed economies. This paper presents simple labor-constrained Kaleckian models and uses these models to compare the implications of financialization under labor-constrained and dual-economy conditions. The paper complements the analysis in Skott and Ryoo (2008) which did not include labor-constrained Kaleckian economies. We show that for plausible parameter values the financial changes commonly associated with fiancialization tend to be expansionary in both dual-economy and labor-constrained settings.
Keywords: E12; E44; 330; financialization; stock-flow consistency; labor constraints; Kaleckian model; Monetäre Wachstumstheorie; Postkeynesianismus; Finanzsektor; Arbeitsangebot; Dualökonomie; Theorie; Monetäre Wachstumstheorie; Postkeynesianismus; Finanzsektor; Arbeitsangebot; Dualökonomie; Theorie